Kajian Yuridis Perbuatan Melanggar Hukum Yang Dilakukan Oleh Penjual Skincare Yang Iklannya Menyesatkan Berdasarkan Pasal 1365 KUHPerdata - Rhevy Permadi (CV Rewang Rencang, 2025)
The cosmetics industry, particularly skincare, in Indonesia is growing rapidly in line with advances in technology and digital media. Competition has led businesses to use aggressive advertising, but this is often misleading, as in the cases of Daviena Skincare and Dr. Richard Lee. These practices harm consumers and violate the principle of honesty. This study aims to analyze the criteria for misleading skincare advertisements based on Article 1365 of the Civil Code, BPOM Regulations No. 18/2024 and No. 32/2021, as well as the forms of legal protection for consumers. Using a normative juridical method, the results of this study show that advertisements that do not correspond to facts are classified as unlawful acts and violate BPOM regulations. Legal protection is provided preventively through regulations and distribution permits, as well as repressively through administrative, civil, and criminal sanctions. This study emphasizes the importance of synergy between the government, business actors, and consumers in creating ethical and lawful advertising.